Investigating the role of poultry in livelihoods and the impact of avian flu on livelihoods outcomes in Africa: Evidence from Ethiopia, Ghana, Kenya, and Nigeria - Birol, Ekin; Asare-Marfo, Dorene; Ayele, Gezahegn; Mensa-Bonsu, Akwasi; Ndirangu, Lydia; Okpukpara, Benjamin; Roy, Devesh; Yakhshilikov, Yorbol (International Food Policy Research Institute, 2010)
In this paper we investigate the role of poultry in households' livelihoods portfolios and the impact of supply-and-demand shocks that may be caused by highly pathogenic avian influenza (HPAI) on households' various livelihoods outcomes in four Sub-Saharan African (SSA) countries. The study countries include Ethiopia and Kenya in East Africa and Ghana and Nigeria in West Africa. These countries represent a spectrum of SSA countries regarding disease status, means of disease spread, and the role of the poultry sector in the economy. By using nationally representative household-level secondary data and discrete choice methods (probit and zero-inflated negative binomial models), we profile the household, farm, and regional characteristics of those households that are most likely to keep poultry and those households that are most likely to be engaged in intensive poultry production (that is, to keep larger household flocks). We estimate the ex ante impact of HPAI outbreaks and scares/threats on livelihoods outcomes by using the propensity score matching approach. The results of this study generate valuable information regarding the role of poultry in the livelihoods of small-scale poultry-producing households and the livelihoods impacts of HPAI-induced supply-and-demand shocks. Such information is critical for the design of targeted, and hence effective, HPAI control and mitigation policies.